2021
DOI: 10.1021/acsami.1c02593
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Persistent Photoconduction with IGZO/ZnON-Tandem-Structure Visible–Near-Infrared Phototransistors

Abstract: Indium–gallium–zinc oxide- and zinc oxynitride-based heterojunction phototransistors were successfully demonstrated to control the persistent photoconduction (PPC) effect and be also responded sensitively at the range from visible to near-infrared. ZnON plays a key role in extending the spectral response at various frequencies of operation. The devices show significantly different photoresponse and photorecovery characteristics depending on the number of stacked layers of IGZO and ZnON. After negative bias and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Since ZnON has an indirect energy bandgap, n = 2 in Equation ( 2). [36,37] Moreover, ZnON exhibited a bandgap of 1.66 eV, which is slightly wider than previously reported values, [38,39] which resulted from the annealing process changing the oxygen and nitrogen concentrations in the ZnON layer (Figure S5b,c and Note S4, Supporting Information). The bandgaps of InAs-ME and InAs-InCl 3 were calculated from the first exciton energy in the UV-vis spectra (Figure S2a, Supporting Information), and the total energy band diagrams are shown in Figure 2g.…”
Section: Resultsmentioning
confidence: 67%
“…Since ZnON has an indirect energy bandgap, n = 2 in Equation ( 2). [36,37] Moreover, ZnON exhibited a bandgap of 1.66 eV, which is slightly wider than previously reported values, [38,39] which resulted from the annealing process changing the oxygen and nitrogen concentrations in the ZnON layer (Figure S5b,c and Note S4, Supporting Information). The bandgaps of InAs-ME and InAs-InCl 3 were calculated from the first exciton energy in the UV-vis spectra (Figure S2a, Supporting Information), and the total energy band diagrams are shown in Figure 2g.…”
Section: Resultsmentioning
confidence: 67%
“…Since the E CBM of ZnON is lower than that of IGZO, the probability for recombination between accumulated electrons in the CBM of ZnON and ionized V O states of IGZO becomes higher. 54 We found that the E CBM of ZnON 5 was lower than that of ZnON 4, which would enhance the recombination capability of ZnON 5 with the ionized V O states of IGZO. At the same time, the accumulated electrons are more likely to recombine with a higher VBM of ZnON 5 in Hetero 2 TFT than ZnON 4 in Hetero 1 TFT.…”
Section: ■ Resultsmentioning
confidence: 72%
“…All recombination mechanisms (1–3) contributed to a much faster decay of the drain current in Hetero 1 and Hetero 2 TFT, which was not possible in IGZO TFT. Since the E CBM of ZnON is lower than that of IGZO, the probability for recombination between accumulated electrons in the CBM of ZnON and ionized V O states of IGZO becomes higher . We found that the E CBM of ZnON 5 was lower than that of ZnON 4, which would enhance the recombination capability of ZnON 5 with the ionized V O states of IGZO.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…1 c through the transient curve. Oxide semiconductors have the problem of persistent photocurrent (PPC), which is increased dark current under periodic light signals caused by ionized oxygen vacancies (V o 2+ ) during the photoresponse 22 . The RF-PTs maintained a photocurrent and did not show a PPC phenomenon during repeated photoresponse.…”
Section: Resultsmentioning
confidence: 99%